Kebiasaan Bermain Game Online Dengan Resiko ADHD (Attention Deficit/Hiperactivity Disorder) Pada Remaja Laki-laki - Ishariani, Linda; Nian Afrian Nuari; Windy Sri Wulandari (STIKES dan AKZI Karya Husada Kediri, 2024)
The habit of playing online games can have a bad impact on teenagers. Teenagers with online game addiction tend to experience ADHD symptoms such as impulsive behavior, inattention and hyperactivity. The aim of this research was to determine the relationship between the habit of playing online games and the risk of ADHD in adolescents at SMPN 1 Rejoso, Nganjuk Regency. This research design was Correlational. The independent variable was the habit of playing online games and the dependent variable is the risk of ADHD. The sample size was 36 respondents each using total sampling. . Data were collected using a questionnaire and data were analyzed using the Rho Spearman test. The research results showed that most of the habits of playing online games were in the moderate category (63.9%). ADHD risk showed that the majority of respondents have a mild ADHD risk category (55.6%). The Rho Spearman test results showed a p-value of 0.019 < 0.05, meaning there is a relationship between the habit of playing online games and the risk of ADHD. One of the external factors for the emergence of ADHD symptoms is environmental factors, for example excessive use of gadgets, especially use of online games. Teenagers can reduce the habit of playing online games, for example by doing other more useful activities such as joining organizations and parents can pay attention to their children when using smartphones, for example by checking the contents of their children's smartphones so that the risk of ADHD can be minimized..